Pengembangan Aplikasi Perencana Wisata “Plesir” Berbasis Web - Sepriadi, Hilman; Rachmadi, Muhammad (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2019)
Indonesia is a country that has extraordinary natural wealth, both from the sea and the land. Not only natural tourism, art tourism, even culinary tourism is no less interesting. The many of tourist objects makes tourists confused to choose which tourist objects to visit and indeed according to their interests, given the limited time to travel. This time limitation makes it difficult for tourists to schedule their tour plans, such as how many tourist attractions can he actually visit with the tour time he has. Moreover, to choose a tourist attraction that suits the interests of each tourist, information about the tourist attraction itself is needed. The limitations of promotional media that can be used by UMKM create many limitations between UMKM and tourists. For this reason, it is necessary to develop a "Plesir" Tourism Planning Application Based on Web using the RUP (Rational Unified Process) methodology. While the steps taken are inception, elaboration, construction and transition. The results of developing this application are making it easier for tourists to use tourism, can get more information about tourist attractions and help UMKM in promoting their products.